Physically active bioreactors for tissue engineering applications - Castro, N. (2020)
Tissue engineering (TE) is a strongly expanding research area. TE approaches require biocompatible scaffolds, cells, and different applied stimuli, which altogether mimic the natural tissue microenvironment. Also, the extracellular matrix serves as a structural base for cells and as a source of growth factors and biophysical cues. The 3D characteristics of the microenvironment is one of the most recognized key factors for obtaining specific cell responses in vivo, being the physical cues increasingly investigated. Supporting those advances is the progress of smart and multifunctional materials design, whose properties improve the cell behavior control through the possibility of providing specific chemical and physical stimuli to the cellular environment. In this sense, a varying set of bioreactors that properly stimulate those materials and cells in vitro, creating an appropriate biomimetic microenvironment, is developed to obtain active bioreactors. This review provides a comprehensive overview on the important microenvironments of different cells and tissues, the smart materials type used for providing such microenvironments and the specific bioreactor technologies that allow subjecting the cells/tissues to the required biomimetic biochemical and biophysical cues. Further, it is shown that microfluidic bioreactors represent a growing and interesting field that hold great promise for achieving suitable TE strategies